Chaos suppression on a class of uncertain nonlinear chaotic systems using an optimal H∞ adaptive PID controller - Alfi, Alireza (Chaos, solitons and fractals, 2012)
► This paper proposes a powerful and flexible method for controlling a class of nonlinear chaotic systems. ► This method is incorporated with H-infinity tracking control scheme. ► In the core of proposed method, PSO algorithm is employed to obtaining an optimal performance. This paper introduces an optimal H∞ adaptive PID (OHAPID) control scheme for a class of nonlinear chaotic system in the presence system uncertainties and external disturbances. Based on Lyapunov stability theory, it is shown that the proposed control scheme can guarantee the stability robustness of closed-loop system with H∞ tracking performance. In the core of proposed controller, to achieve an optimal performance of OHAPID, the Particle Swarm Optimization (PSO) algorithm is utilized. To show the feasibility of proposed OHAPID controller, it is applied on the chaotic gyro system. Simulation results demonstrate that it has highly effective in providing an optimal performance.